An exploration of emotional protection and regulation in nurse–patient interactions: The role of the professional face and the emotional mirror. Issue 4 (December 2015) - Cecil, Penelope; Glass, Nel
Summary: Introduction: While interpersonal styles of nurse–patient communication have become more relaxed in recent years, nurses remain challenged in emotional engagement with patients and other health professionals. In order to preserve a professional distance in patient care delivery however slight, nurses need to be able to regulate their emotions. Aim: This research aimed to investigate nurses' perceptions of emotional protection and regulation in patient care delivery. Methods: A qualitative approach was used for the study utilising in-depth semi-structured interviews and researcher reflective journaling. Participants were drawn from rural New South Wales. Following institutional ethics approval 5 nurses were interviewed and reflective journaling commenced. The interviews and the reflective journal were transcribed verbatim. Results: The results revealed that nurses' emotional regulation demonstrated by a 'professional face' was an important strategy to enable delivery of quality care even though it resulted in emotional containment. Such regulation was a protective mechanism employed to look after self and was critical in situations of emotional dissonance. The results also found that nurses experience emotional dissonance in situations where they have unresolved personal emotional issues and the latter was a individual motivator to manage emotions in the workplace. Conclusion: Emotions play a pivotal role within nurse–patient relationships. The professional face can be recognised as contributing to emotional health and therefore maintaining the emotional health of nurses in practice. This study foregrounds the importance of regulating emotions and nurturing nurses' emotional health in contemporary practice.